Analisis Penerapan Konsep Value for Money pada Pemerintah Kabupaten Bantul - Kurniawati, Nova; Adhivinna, Vidya Vitta (Akmenika, 2016)
The performance of The goverment institutions is now under the spotlight along withthe improvement in public awareness on the course of general publicadministration.People are getting more and more intelligent and critical. They havedemand for transparancy, clean, economical, effectual, responsive and accountable.The aim of this research is to discover the financial performance of PemerintahKabupaten Bantul during year 2010-2013. The test was done by using value formoney method to measure the financial performance from the perspective ofeconomy, effectiveness and efficiency which has shown in the annual budgetaryreport and realization from 2010-2013. The result from financial analysis onPemerintah Kabupaten Bantul has shown that in economic perspective the financialmanagement in Bantul can be said to be economical in year 2010 and getting betterin 2011-2013. From effectiveness it can be said to be very effectual from 2010 till2013, and from efficiency perspective Bantul Administration was not efficient in2010, but in 2011 can be said to be very efficient and then in 2012-2013 can be saidto be inefficient.